Cigarette brand diversity and price changes during the implementation of plain packaging in the United Kingdom - Breton, Magdalena Opazo; Britton, John; Huang, Yue; Bogdanovica, Ilze (Wiley, 2018)
Background and aim: Plain packaging of cigarettes appeared in the UK in July 2016 and was ubiquitous by May 2017. The change coincided with another legislative change, raising the minimum pack size from 10 to 20 cigarettes. Laws imposing plain packaging on cigarette packs remove another promotional route from tobacco companies but the effect of such laws on brand diversity, pricing, and sales volume is unknown. This study aimed to 1) describe and quantify changes in brand diversity, price segmentation and sales volumes and 2) estimate the association between the introduction of plain cigarette packaging and cigarette pricing in the UK. Design: We used a natural experiment design to assess the impact of plain packaging legislation on brand diversity and cigarette prices. The data comprised a sample of 76% of sales of cigarettes in the UK between March 2013 and June 2017. Setting: United Kingdom Measurements: Cigarette prices, number of brands and products, volumes of sales Findings: During the period analysed, there was a slight decrease in the number of cigarette brands. There was also an initial increase observed in the number of cigarette products, mainly due to an increase in the number of products in packs of fewer than 20 cigarettes sold before July 2016, which was then followed by a rapid decrease in the number of products that coincided with the implementation of the new legislation. Cigarette sales volumes during this period did not deviate from the preceding secular trend, but prices rose substantially. Regression results showed that price per cigarette, regardless of pack size, was 5.0 (95% CI 4.8 to 5.3) pence higher in plain than in fully branded packs. For packs of 20 cigarettes, price increases were greater in the lower price quintiles, ranging from 2.6 (95% CI 2.4 to 2.7) GBP in the lowest to 0.3 (95% CI 0.3‐0.4) GBP per pack in the highest quintile. Conclusions: The implementation of standardised packaging legislation in the UK, which included minimum pack sizes of 20, was associated with significant increases overall in the price of manufactured cigarettes but no clear deviation in the ongoing downward trend in total volume of cigarette sales.